Forming a dualistic system in the Habsburg Empire: prerequisites and peculiarities of building new relations between Austria and Hungary - Vinogradnyi, B. A. (Гуманитарные и юридические исследования, 2024)
Introduction. After its reformation in 1867, AustroHungary became a unique state entity that abandoned strict centralization and implemented a unique formula of constitutional development. This resulted in a personal union between Austria and Hungary, which adopted different models of domestic and economic development. The establishment of the European Union, the development of multiculturalism, and the increasing role of regions in the development of individual states and the EU as a whole stimulate interest in the history of the Habsburg Empire. Materials and Methods. Both foreign and, to a lesser extent, domestic historiography note the interest of scientific community in Austro-Hungary and its place in world history. However, the debate on this topic is only intensifying. Different schools and directions either idealize the Habsburg Empire or consider it an “anachronism” in Europe. In the course of working on this topic, legislative acts that laid the foundation of the dualistic system were used as historical sources. The author applied the principles of historicism, objectivity, and systematics in his work on the material. Analysis. The article emphasizes that even before the defeat in the Austro-Prussian war, the monarchy attempted to reach a compromise with Hungary, which held an exceptional place in the empire and had a “historical right” to restore its own statehood. The war only accelerated this process and contributed to the formation of the dualistic system. Austria and Hungary effectively became independent state entities united by a common monarch and the socalled common affairs. The approval of dualism by the parliaments of both halves of the empire became the basis for its construction. Constitutionalism and liberalism were to ensure its observance in the future. Results. The dualistic monarchy resulted from a compromise between Austro-Germans and Hungarians, the monarchy, and Hungary. Dualism provided stable development for Austro-Hungary in the last third of the 19th century and the early 20th century. However, the rise of minority national movements required reforming dualism and creating a fundamentally different system.